Hatenography : an analysis of hate speech on Facebook in 2019 Indonesian presidential campaign - Bajari, Atwar; Koswara, Iwan; Erlandia, Dedi Rumawan (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article discusses hate speech on Facebook from two groups of supporters for the presidential candidates in the 2019 Presidential Election in Indonesia. The study used a virtual ethnography approach to analyze cultural groups or communities through their conversations on the Facebook platform. Data collection was conducted by observing and collecting words, phrases, and sentences in the Official Facebook account of two presidential candidates in the 2019 Presidential Election and statements of both presidential and vice-presidential candidates in 2019. In addition, researchers also observed three voluntary group accounts for each candidate. Therefore, the total number of accounts observed was eight. Data was analysed with Nvivo 12+ to obtain statistics on the strength of the chosen speech word and the dominant phrase or word that appears. The result shows that specific phrases or terms to intimidate each supporter of both parties in massive numbers appeared in the form of hate speech during the campaign. The purpose of the hate speech is to insult/humiliate, intimidate or accuse others of doing something inappropriate or evil (accusation which involves sarcasm and foul language directed to the opponent. Candidates also provoked each other by accusing the other party of being stupid, disgusting, pathetic, ugly, and retarded. The implication was that hate speech has disunited the public on the social media space. Accusing and attaching bad characters to other groups through hate speech has strengthened inter-group stereotypes and formed an unhealthy democratic climate.